2003
DOI: 10.1124/dmd.31.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Metabolism of Idarubicin to Idarubicinol in Rat Heart: Effect of Rutin and Phenobarbital

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Since the severe cardiotoxicity of anthracyclines has been attributed to the intramyocardial formation of C-13 alcohol metabolites, the kinetics of cardiac metabolite formation and disposition as well as the effect of carbonyl reductase inhibitors are of specific interest. This study was designed to investigate the effect of rutin and phenobarbital on the pharmacokinetics of idarubicin (IDA) and its conversion to idarubicinol (IDOL) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Quercetin has better cardioprotective effects against DOX cardiotoxicity, and it could significantly inhibit the metabolic conversion of DOX to doxorubicinol (Vaclavikova et al 2008 ). The aldo–keto reductase inhibitors phenobarbital and rutin also could alter the metabolism, pharmacokinetics, and toxicity of anthracycline (Behnia and Boroujerdi 1999 ; Kang and Weiss 2003 ). However, it has not been reported that flavonoids can diminish heart exposure to DOX.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has better cardioprotective effects against DOX cardiotoxicity, and it could significantly inhibit the metabolic conversion of DOX to doxorubicinol (Vaclavikova et al 2008 ). The aldo–keto reductase inhibitors phenobarbital and rutin also could alter the metabolism, pharmacokinetics, and toxicity of anthracycline (Behnia and Boroujerdi 1999 ; Kang and Weiss 2003 ). However, it has not been reported that flavonoids can diminish heart exposure to DOX.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] Therefore, for simulating DOX concentration over the bioreactors, the aforementioned Equations () and () were used and the corresponding parameters were accordingly extracted from the literature. [ 37–39,52,53 ]…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, recent studies conducted by perfusing rat heart with IDA have shown that a major pool of IDAol would be formed in the vascular wall rather than in cardiomyocytes, transiently increasing coronary resistance rather than inducing negative inotropism (Kang and Weiss, 2003). These findings indicate that an additional determinant of cardiac toxicity or tolerability pertains to the compartment within which alcohol metabolites are formed and suggest that anthracyclines undergoing metabolization in cellular types other than cardiomyocytes might prove to induce different patterns of cardiotoxicity compared with anthracyclines' exhibiting preferred metabolization in the vulnerable myocytes.…”
Section: Advances In Apoptosismentioning
confidence: 99%